2016
DOI: 10.4103/1735-1995.192509
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of platelet-to-lymphocyte ratio in severe degenerative aortic valve stenosis

Abstract: Background:Aortic valve stenosis (AVS) is the most common cause of left ventricular outflow obstruction, and its prevalence among elderly patients causes a major public health burden. Recently, platelet-to-lymphocyte ratio (PLR) has been recognized as a novel prognostic biomarker that offers information about both aggregation and inflammation pathways. Since PLR indicates inflammation, we hypothesized that PLR may be associated with the severity of AVS due to chronic inflammation pathways that cause stiffness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 17 publications
(16 reference statements)
1
9
0
Order By: Relevance
“…They were shown to possess predictive and/or prognostic roles in various CVD situations 10–12 . Evidence coming from previous studies demonstrated their predictive capacity also in severe AS 6–9 . In addition, increased NLR levels were found to be linked with short‐ and long‐term mortality in patients with AS undergoing aortic valve replacement surgery 21 .…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…They were shown to possess predictive and/or prognostic roles in various CVD situations 10–12 . Evidence coming from previous studies demonstrated their predictive capacity also in severe AS 6–9 . In addition, increased NLR levels were found to be linked with short‐ and long‐term mortality in patients with AS undergoing aortic valve replacement surgery 21 .…”
Section: Discussionmentioning
confidence: 98%
“…TA B L E 2 Echocardiographic measurements of the study population demonstrated their predictive capacity also in severe AS. [6][7][8][9] In addition, increased NLR levels were found to be linked with shortand long-term mortality in patients with AS undergoing aortic valve replacement surgery. 21 Similarly, Condado et al showed that elevated NLR and PLR levels are associated with the occurrence of 30-day adverse outcomes in patients treated with transcatheter aortic valve replacement.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While we utilized IL-6 and hsCRP to monitor inflammation in our patient population, recent literature has suggested that other markers such as platelet-to-lymphocyte ratio and neutrophil-to-lymphocyte ratio may also accurately reflect inflammatory levels and have prognostic value in other inflammatory conditions. 25,26 While our study was not powered to answer these questions in a CV disease population, more research in this area will certainly be needed to further elucidate the role that these biomarkers could potentially play in coronary artery disease prognostication and management in the future.…”
Section: Discussionmentioning
confidence: 99%